Biology Learning Models Based on Higher Order Thinking Skills; A Book Research and Development - Jodion Siburian; Ali Sadikin (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop a biology learning model book based on Higher Order Thinking Skills (HOTS) to meet the demand for effective teaching resources in biology education. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was used to ensure a systematic development process. An initial survey involving 80 respondents revealed that 86.5% of respondents "strongly needed" the book, while 13.5% "needed" it, indicating a significant demand among prospective biology teachers. The book underwent a rigorous validation process, including two rounds of expert review, where the first validation yielded a score of 67 (not valid) and the second validation improved to 82 (valid). Additionally, trials were conducted in two phases: a small group trial with 6 students and a large group trial with 15 students. Results from the small group trial showed that 50% of respondents rated the book as "Good," 33% rated it as "Very Good," and 17% rated it as "Fair." In the large group trial, 60% of respondents rated the book as "Good," while 40% rated it as "Very Good." The book effectively integrates HOTS principles, which have been shown to enhance students' critical thinking and problem-solving skills. These findings affirm that this guidebook not only addresses the urgent need in biology education but also has significant potential to improve educational quality by providing a structured approach to implementing HOTS in the classroom.